Evaluation of Absolute Neutrophil Count, Band Count and Morphological Changes in Neutrophils in Bacterial Infections - Saadia Latif, Hamid Iqbal, Jawad Zafar, Tamoor Chughtai, Saadat Parveen, Aayza Mujahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the absolute neutrophil count, band count and morphological changes in diagnosing acute bacterial infections among patients presenting with acute febrile illness. Methodology: It was cross sectional analytical study conducted after taking approval from institutional ethical review committee. Total 726 patients were included. The cut-off for leukocytosis was 19.6x109/l. Counted 200 WBC. Band cells were counted according to College of American Pathologists Survey criteria. If band count is 20%, it is considered an increased count. Chi square test was applied. Results: The Acute neutrophil count was elevated significantly in positive cases (p<0.01). Band cells were elevated in +ve cases when comparing with their counterpart (p<0.01). The morphological changes in neutrophils in both culture positive and negative samples showed that toxic granules were seen in > ¾ samples, Dohle bodies in 80.9% and vacuoles in 69.1% culture positive cases. Conclusion: Study findings indicate that ANC and band count is significantly higher in patients with acute bacterial infection. Keywords: Neutrophil, Toxic granulation, Bacterial infections